2009
DOI: 10.1159/000225971
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in the Mesenteric Artery and Disturbed Nonadrenergic Noncholinergic Relaxation of the Ileum due to Intestinal Ischemia-Reperfusion Can Be Prevented by Sildenafil

Abstract: The aim of the present study was to evaluate the effects of sildenafil on endothelium-dependent mesenteric artery vasorelaxation and nonadrenergic noncholinergic (NANC) ileal responses in an experimental rat intestinal ischemia-reperfusion (I/R) model. The superior mesenteric artery was occluded for 45 min of ischemia and then the clamp was removed for 60 min of reperfusion. Sildenafil (1 mg/kg, i.v.) or saline was administered prior to surgery in the I/R and sham-operated groups. Acetylcholine-induced relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
2
1
4
Order By: Relevance
“…Data are shown as mean Ϯ SEM from 5 animals. *P < 0.05 sham versus I/R by Student's unpaired t-test. vasodilatation (Kedzierski and Yanagisawa, 2001;Gourdin et al, 2009), although discrepancies have been reported (Koksoy et al, 2000;Seal and Gewert, 2005;Gourdin et al, 2009;Soydan et al, 2009). However, in our study, vasodilatation to ACh was similar in sham and I/R rats.…”
Section: Figure 10contrasting
confidence: 57%
See 1 more Smart Citation
“…Data are shown as mean Ϯ SEM from 5 animals. *P < 0.05 sham versus I/R by Student's unpaired t-test. vasodilatation (Kedzierski and Yanagisawa, 2001;Gourdin et al, 2009), although discrepancies have been reported (Koksoy et al, 2000;Seal and Gewert, 2005;Gourdin et al, 2009;Soydan et al, 2009). However, in our study, vasodilatation to ACh was similar in sham and I/R rats.…”
Section: Figure 10contrasting
confidence: 57%
“…On the other hand, endothelium‐dependent vasodilatation has been demonstrated to be more affected by I/R injuries than vasoconstriction and endothelium‐independent vasodilatation (Kedzierski and Yanagisawa, 2001; Gourdin et al ., 2009), although discrepancies have been reported (Koksoy et al ., 2000; Seal and Gewert, 2005; Gourdin et al ., 2009; Soydan et al ., 2009). However, in our study, vasodilatation to ACh was similar in sham and I/R rats.…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente, a exposição crônica a um agonista pode causar desacoplamento entre o receptor e as proteínas efetoras e/ ou uma diminuição na regulação desse receptor (Stiles et al, 1984). Por conseguinte, Wallach e colaboradores (1980) sugeriram que em situações de isquemia e reperfusão, como no caso da cirurgia cardíaca, ocorre elevação dos níveis plasmáticos de catecolaminas.…”
Section: Discussionunclassified
“…Além da ativação da AMPK, outros estudos demonstram que o tratamento agudo com estatina em células endoteliais é também capaz de ativar a fosforilação da eNOS por meio de proteína quinase A (PKA) e Akt (Harris et al, 2004;Sun et al, 2006).…”
Section: Introductionunclassified
“…Em situações clínicas, como inflamações, infecções, trauma oclusivo arterial, parada cardíaca, trombose, embolia, vasoespasmo, tumores, transplantes e em cirurgias com o uso de oclusores vasculares, são inúmeras as oportunidades para a indução de hipoxia tissular pela falta de oxigênio. Essa deficiência do aporte sangüíneo (isquemia) é conseqüência da diminuição da luz das artérias, arteríolas, vênulas e capilares (WELBOURN et al, 1991;SOYDAN et al, 2009). Após a restituição do fluxo sanguíneo (reperfusão), metabólitos produzidos em situação de isquemia geram radicais livres altamente reativos que acentuam a lesão tecidual local ou sistêmica (LEWIS et al, 1999;CARDEN e GRANGER, 2000;DE PERROT et al, 2003;ROLO et al, 2009;NILAKANTAN et al, 2009).…”
Section: Introductionunclassified